2020
DOI: 10.1021/acs.chemmater.9b05403
|View full text |Cite
|
Sign up to set email alerts
|

Superionic Lithium Intercalation through 2 × 2 nm2 Columns in the Crystallographic Shear Phase Nb18W8O69

Abstract: Nb18W8O69 (9Nb2O5×8WO3) is the tungsten-rich end-member of the Wadsley-Roth crystallographic shear (cs) structures within the Nb2O5-WO3 series. It has the largest block size of any known, stable Wadsley-Roth phase, comprising 5 ´ 5 units of corner-shared MO6 octahedra between the shear planes, giving rise to 2 nm ´ 2 nm blocks. Rapid lithium intercalation is observed in this new candidate battery material and 7 Li pulsed field gradient nuclear magnetic resonance spectroscopy-measured in a battery electrode for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 49 publications
6
51
0
Order By: Relevance
“…Recently, Griffith and Grey have applied 7 Li pulsed-eldgradient nuclear-magnetic-resonance (PFG-NMR) spectroscopy to probe Li + diffusion in Nb 18 W 8 O 69 at room temperature (298 K). 19 The technique is generally not suitable for measuring diffusion in battery electrodes, since Li + mobility is too slow in most electrode materials. However, since the diffusion coefficients for Li + in Wadsley-Roth type materials are orders of magnitude greater than in many battery electrode materials, PFG-NMR spectroscopy measurements are possible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Griffith and Grey have applied 7 Li pulsed-eldgradient nuclear-magnetic-resonance (PFG-NMR) spectroscopy to probe Li + diffusion in Nb 18 W 8 O 69 at room temperature (298 K). 19 The technique is generally not suitable for measuring diffusion in battery electrodes, since Li + mobility is too slow in most electrode materials. However, since the diffusion coefficients for Li + in Wadsley-Roth type materials are orders of magnitude greater than in many battery electrode materials, PFG-NMR spectroscopy measurements are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, rapid lithium mobility has been identied in a selection of niobium-based complex oxides with open framework structures, including H-and T-Nb 2 O 5 , [13][14][15] 19 High charging and discharging rates can be achieved in many of these materials even in large, micrometer-sized particles. They display low voltage vs. Li/Li + and as such, they are of interest as high-rate Li-ion anode materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This report confirmed that T-Nb 2 O 5 stores lithium mainly through intercalated pseudocapacitance (Nb 2 O 5 þ xLi þ þ xe À ⇔Li x Nb 2 O 5 ) through in situ XRD and kinetic studies. Specifically, the diffraction peaks of the crystal plane (001) and (180) are slightly periodically shifted due to the embedding Li þ in the energy storage process. Clearly, the crystal structure of T-Nb 2 O 5 will not be damaged during the Li þ embedding process and maintains good cyclic stability (retains 98% capacity after 1000 cycles).…”
Section: Introductionmentioning
confidence: 99%